THE HISTORICAL ROLE AND SCHOLARLY HERITAGE OF ZAKHIRIDDIN MUKHAMMAD BABUR - Mirhakimova Feruza Xoldorjon qizi,; Valijonova Manzura Vohidjon kizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation: Zakhiriddin Mukhammad Babur was one of the greatest figures of his  time  and  left  an  invaluable  scholarly  and  literary  legacy.  This  article  analyzes Babur’s role as a historical personality, his contributions to state governance, literature, and the development of science, as well as the significance of his scholarly and spiritual heritage. Babur was one of the outstanding representatives of the Eastern Renaissance of the 15th-16th centuries. He was not only the founder of a powerful empire and a skilled military commander, but also a prominent poet, historian, and geographer. In particular, Babur’s work Baburnama is regarded as a highly valuable historical and geographical source. Moreover, his poetic legacy, contributions to the theory of aruz prosody, and his role in establishing a literary school are of exceptional importance.